2021
DOI: 10.3390/ijms22063048
|View full text |Cite
|
Sign up to set email alerts
|

In Translation: FcRn across the Therapeutic Spectrum

Abstract: As an essential modulator of IgG disposition, the neonatal Fc receptor (FcRn) governs the pharmacokinetics and functions many therapeutic modalities. In this review, we thoroughly reexamine the hitherto elucidated biological and thermodynamic properties of FcRn to provide context for our assessment of more recent advances, which covers antigen-binding fragment (Fab) determinants of FcRn affinity, transgenic preclinical models, and FcRn targeting as an immune-complex (IC)-clearing strategy. We further comment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 226 publications
(323 reference statements)
0
25
0
1
Order By: Relevance
“…antibody recycling). It has been shown that in some tissues such as intestine, FcRn is important for the transcytosis of IgG through the epithelia, whereas FcRn-mediated transcytosis through endothelial cells may be a prerequisite for autoantibodies to gain access to their target tissues (reviewed in [32,34]). Therefore, we propose that in tissues such as the epidermis, FcRn may function in "seeding immunity" by transporting the soluble, monomeric autoantibodies towards the autoantibody target cells, epidermal keratinocytes in pemphigus (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibody recycling). It has been shown that in some tissues such as intestine, FcRn is important for the transcytosis of IgG through the epithelia, whereas FcRn-mediated transcytosis through endothelial cells may be a prerequisite for autoantibodies to gain access to their target tissues (reviewed in [32,34]). Therefore, we propose that in tissues such as the epidermis, FcRn may function in "seeding immunity" by transporting the soluble, monomeric autoantibodies towards the autoantibody target cells, epidermal keratinocytes in pemphigus (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FcRn appears to mediate the lysosomal degradation of autoantibody-antigen immune complexes (IC) in the target cells of the autoantibodies [31,32,33]. A recent review by Qi and Cao is recommended for a thorough summary of FcRn functions [34]. Although it has been shown that keratinocytes endogenously express FcRn [35], a potential direct role of FcRn in the pathogenesis of pemphigus and in the transport of autoantibodies in keratinocytes has so far not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For the complexation study described in the simulation set 1, following a previous study ( 43 ), the pHs 7.0 and 4.6 were chosen, respectively, due to the need to understand the behavior of the system in physiologic pH level conditions and the acidic pH of the endosomal environment. This is a reasonable choice to keep the general features of the present study even though the precise value of the pH in human cells can be slightly different from these numbers ( 111 ). For all simulations from set 2, pH was varied from 0 to 14 with an increment of 0.1 units of pH to explore all possible pH conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Linking insulin to the fragment crystallizable (Fc) region of immunoglobulin G (IgG) extends the insulin's half-life because the fusion protein benefits from the same recycling pathway that confers a relatively long half-life to endogenous IgG [55,56]. When IgG is taken up by cells through micropinocytosis, the Fc region binds to the membranebound neonatal Fc receptor (FcRn) in acidified endocytic vesicles.…”
Section: Once-weekly Formulations: Technological Principlesmentioning
confidence: 99%